Energy loss of laser-accelerated ions in dense ionized matter. Issue 19 (January 2020) - Zhao, Y; Ren, J; Deng, Z; Qi, W; Cheng, R; Wang, X; Liu, W; Ma, B; Yin, S; Chen, B; Feng, J; Wang, S; et al.
Synopsis: Knowledge about the energy loss of heavy ion in dense ionized matter is of great importance in fields such as inertial confinement fusion, fast ignition as well as intense heavy ion beam driven high energy density physics. The energy loss of 3.4 MeV proton in TAC foam plasma was measured on the XGIII laser facility. It was found that the measured energy loss is far above the Beth prediction.